1992
DOI: 10.1039/ft9928800615
|View full text |Cite
|
Sign up to set email alerts
|

Highly resolved electron paramagnetic resonance spectrum of copper(II) ion pairs in CuCe oxide

Abstract: Avenue Albert Einstein, 69626 Vi/leurbanne, France A copper-cerium oxide sample prepared with an atomic ratio, Cu : Ce, of 0.01 has been studied by electron paramagnetic resonance (EPR) spectroscopy. A well resolved spectrum of copper(11) ion pairs has been evi denced and the hyperfine structure of the perpendicular components clearly appears. The high resolution can be explained by the presence of two nearly equivalent Cu2+ ions separated by an oxygen ion. A correlation in EPR parameters has been found betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 35 publications
4
48
0
Order By: Relevance
“…This feature has been previously ascribed to either superoxide species adsorbed on Ce 4þ ions (O 2 À -Ce 4þ ) [37] or partially reduced (Cu 2þ -Ce 3þ ) species. [38] The simultaneous existence of signals K and D detected at higher Cu concentrations in FSP-prepared catalysts can be rationalized by the following argument: while K originates from two oxygen-bridged Cu nuclei, [36] these dimers facilitate the formation of doubly charged oxygen vacancies in the CeO 2 lattice, as indicated by the XPS and Raman results. It is proposed the electrons localized at these vacancies can react with nearby Ce 4þ , which subsequently leads to an intensification of the D-type signal.…”
Section: Copper Speciation and Support Interactionsmentioning
confidence: 95%
See 3 more Smart Citations
“…This feature has been previously ascribed to either superoxide species adsorbed on Ce 4þ ions (O 2 À -Ce 4þ ) [37] or partially reduced (Cu 2þ -Ce 3þ ) species. [38] The simultaneous existence of signals K and D detected at higher Cu concentrations in FSP-prepared catalysts can be rationalized by the following argument: while K originates from two oxygen-bridged Cu nuclei, [36] these dimers facilitate the formation of doubly charged oxygen vacancies in the CeO 2 lattice, as indicated by the XPS and Raman results. It is proposed the electrons localized at these vacancies can react with nearby Ce 4þ , which subsequently leads to an intensification of the D-type signal.…”
Section: Copper Speciation and Support Interactionsmentioning
confidence: 95%
“…This is due to interaction between the nuclear spins of two Cu 2þ ions. [36] For FSP catalysts, hyperfine splitting is resolvable at all Cu concentrations, indicating a high degree of crystallization between the Cu and CeO 2 components is achieved. [36] Hyperfine splitting has previously been reported in Cu-CeO 2 systems subject to prolonged periods at elevated temperatures and under vacuum.…”
Section: Copper Speciation and Support Interactionsmentioning
confidence: 96%
See 2 more Smart Citations
“…However, the solubility of copper in the CeO -fluorite lattice must be expected to be low due to the difference in ionic radii. Electron paramagnetic resonance studies (7) showed that CeO containing 1% Cu exhibited surface segregation with an enrichment factor of 25, which supports the assumption of a rather low solubility in the CeO structure. In the related Cu-Zrsystem (8) no ternary compound and a very small solid solubility of copper in the cubic ZrO modification have been reported.…”
Section: Introductionmentioning
confidence: 78%